Расчет и прогнозирование свойств оксидов - Воробьев Юрий Павлович (Наука, 1983)
Экземпляры: КХ (20140619) / Инвентарный номер: 798854 / Цена: 3.40 / Сис.шифр: 546 / Авт.знак: В 75 / ГРНТИ: 31 / ББК: 24